Method selection for sustainability assessments: The case of recovery of resources from waste water. (15th July 2017) - Zijp, M.C.; Waaijers-van der Loop, S.L.; Heijungs, R.; Broeren, M.L.M.; Peeters, R.; Van Nieuwenhuijzen, A.; Shen, L.; Heugens, E.H.W.; Posthuma, L.
Abstract: Sustainability assessments provide scientific support in decision procedures towards sustainable solutions. However, in order to contribute in identifying and choosing sustainable solutions, the sustainability assessment has to fit the decision context. Two complicating factors exist. First, different stakeholders tend to have different views on what a sustainability assessment should encompass. Second, a plethora of sustainability assessment methods exist, due to the multi-dimensional characteristic of the concept. Different methods provide other representations of sustainability. Based on a literature review, we present a protocol to facilitate method selection together with stakeholders. The protocol guides the exploration of i) the decision context, ii) the different views of stakeholders and iii) the selection of pertinent assessment methods. In addition, we present an online tool for method selection. This tool identifies assessment methods that meet the specifications obtained with the protocol, and currently contains characteristics of 30 sustainability assessment methods. The utility of the protocol and the tool are tested in a case study on the recovery of resources from domestic waste water. In several iterations, a combination of methods was selected, followed by execution of the selected sustainability assessment methods. The assessment results can be used in the first phase of the decision procedure that leads to a strategic choice for sustainable resource recovery from waste water in the Netherlands. Graphical abstract: Highlights: Existing sustainability methods differ in their translation of sustainable development. A protocol and tool are proposed for transparent method selection with stakeholders. Application in a case study showed the iterative process of method selection. Careful method selections results in assessments that fit the decision context. Recovery of resources from waste water seems beneficial for the environment.